2012
DOI: 10.1515/1949-6605.6378
|View full text |Cite
|
Sign up to set email alerts
|

Home-Going as a Strategy for Success Among Haudenosaunee College and University Students

Abstract: Recent research on Native American college students has focused on their success in attaining college degrees (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Not validating the existence of the HNAFS by those who do not understand, or care to understand them, can be potentially harmful to Native students as it can be seen as an erasure of their own unique expression in F&S life. This can mislead professionals to think that commonplace practices with non‐Native students will produce favorable results for Native students, which scholars have demonstrated to be false (Larimore & McClellan, ; Lowe, ; Martin ; Martin & Thunder, ; Shotton, Lowe, & Waterman, ; Still, ; Waterman, ).…”
Section: Challenges and Obstacles For Hnafs And Native Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not validating the existence of the HNAFS by those who do not understand, or care to understand them, can be potentially harmful to Native students as it can be seen as an erasure of their own unique expression in F&S life. This can mislead professionals to think that commonplace practices with non‐Native students will produce favorable results for Native students, which scholars have demonstrated to be false (Larimore & McClellan, ; Lowe, ; Martin ; Martin & Thunder, ; Shotton, Lowe, & Waterman, ; Still, ; Waterman, ).…”
Section: Challenges and Obstacles For Hnafs And Native Studentsmentioning
confidence: 99%
“…However, this can have adverse effects on Native students. Waterman () demonstrated that many Native students go where they feel most supported: their home communities. Native students have complex spiritual and cultural needs that institutions are not meeting, so they must seek restoration from their communities (Waterman, ).…”
Section: Recommendations For Student Affairs Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the challenges previously mentioned, research also demonstrates that family and home has a profound influence on empowering Native students in their pathways to college (Rindone 1988;Pavel and Padilla 1993;Guillory and Wolverton 2008;Jackson and Smith 2001;Jackson et al 2003;Heavyrunner and DeCelles 2002;Waterman 2012). For example, Navajo students from very low-income (below $5,999/year) homes mentioned family support was the driving motivation for promoting their academic success (Rindone 1988).…”
Section: Literature and Theory Guiding The Studymentioning
confidence: 99%
“…And when Native students encountered challenges in college, they indicated that family was the most influential factor in helping them to overcome those challenges (Guillory and Wolverton 2008). For some Native students, such as those from the Haudenosaunee Nation, a crucial strategy for their success included being able to return home to family at frequent intervals (Waterman 2012). This is consistent with other research that found that 56.8% of 155 Native students indicated a need to go home compared to 31.6% of Blacks, 24.4% of Hispanics, and 16.7% of Anglos (Benjamin et al 1993).…”
Section: Literature and Theory Guiding The Studymentioning
confidence: 99%